Browser-based Java Development Environment for Programming Education - Liang, Yibao; Uehara, Minoru (International Symposium on Computing and Networking Workshops (Online), 2023)
Programming education has become popular in elementary education. However, the pass rate for the subject of programming in higher education is not always sufficient. In recent years, data science courses have effectively taught interactive and goal-oriented programming using Python and Jupyter. We propose a method for learning Java programming interactively using a Jupyter-like execution environment. This environment also enables the execution of network applications that are difficult to execute in the existing Jupyter environment. We show that many of the actual class examples can be executed using the proposed system.